Molecular surveillance of carbapenem-resistant Enterobacterales in two nearby tertiary hospitals to identify regional spread of high-risk clones in Germany, 2019-2020 - Boutin, Sébastien; Welker, S.; Gerigk, Marlis; Miethke, Thomas; Heeg, Klaus; Nurjadi, Dennis (The journal of hospital infection, 2024)
Background - Understanding the transmission dynamics of carbapenem-resistant Enterobacterales (CRE) is critical to addressing the escalating global threat of antimicrobial resistance (AMR). Although hospital transmission of CRE has been extensively studied, information on community transmission is lacking. - Aim - To identify genomic clusters of CRE from two nearby institutions that may be indicative of community or inter-facility transmission. - Methods - CRE isolates between January 1st, 2019 and December 31st, 2020 from two tertiary hospitals, detected in the respective routine microbiology laboratories, were collected and characterized by short-read whole-genome sequencing. - Findings - A total of 272 CRE were collected, with Enterobacter cloacae complex (71/192, 37%) predominant in Heidelberg and Escherichia coli (19/80, 24%) in Mannheim. The most common carbapenem resistance gene, blaOXA-48, was detected in 38% of CRE from both centres. Several putative transmission clusters were found, including six clusters of E. cloacae complex, five clusters of Klebsiella pneumoniae, four clusters of Citrobacter freundii, and two clusters each of Escherichia coli and K. aerogenes. No clusters involved isolates from both study centres, except for an ST22 C. freundii cluster. Globally circulating clones were identified between the two centres for ST131 E. coli, ST66 E. hormaechei, and ST22 C. freundii. - Conclusion - This study found no widespread transmission clusters among isolates from both centres, suggesting a hospital-specific clonal structure. This suggests that CRE clusters involving both institutions may indicate emerging or circulating clones in the community, highlighting the need for intersectoral surveillance and data sharing.
Online verfügbar: 7. Mai 2024, Artikelversion: 7. Juni 2024
Gesehen am 27.02.2025